2019
DOI: 10.3390/ijerph16224475
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Counselling Related to a Healthy Lifestyle Carried Out by a General Practitioner

Abstract: The aim of the study was to assess whether general practitioners (GPs) monitor and evaluate the health behavior of their patients in the field of a diet, physical activity, and weight control, and whether they provide appropriate counselling as part of this evaluation. Predictors of those activities among physicians were also determined. The cross-sectional study was conducted in the Piotrkowski district among 200 GPs. The questionnaire covered socio-demographic data and lifestyle characteristics of the physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 29 publications
(34 reference statements)
5
32
0
Order By: Relevance
“…Most felt equipped to initiate conversations, and that they were sufficiently knowledgeable about current dietary advice guidelines and recommended levels of physical activity for patients with increased cardiovascular risk factors. Similar findings were reported in studies where primary care physicians reported having adequate knowledge and understanding about the health benefits for patients associated with achieving recommended levels of physical activity [41], even though other work has demonstrated that physical activity is less likely to be discussed with patients compared to other modifiable factors, such as smoking or blood pressure [42]. While there is evidence to suggest that brief interventions can be effective in producing small but significant behavioural changes in patients [43], behaviour change conversations around physical activity can be challenging [44,45].…”
Section: Comparison With Existing Literaturesupporting
confidence: 84%
“…Most felt equipped to initiate conversations, and that they were sufficiently knowledgeable about current dietary advice guidelines and recommended levels of physical activity for patients with increased cardiovascular risk factors. Similar findings were reported in studies where primary care physicians reported having adequate knowledge and understanding about the health benefits for patients associated with achieving recommended levels of physical activity [41], even though other work has demonstrated that physical activity is less likely to be discussed with patients compared to other modifiable factors, such as smoking or blood pressure [42]. While there is evidence to suggest that brief interventions can be effective in producing small but significant behavioural changes in patients [43], behaviour change conversations around physical activity can be challenging [44,45].…”
Section: Comparison With Existing Literaturesupporting
confidence: 84%
“…Similar results were reported in two other studies [42,67]. It appears that healthcare professionals do not sufficiently engage in preventive counselling [68][69][70], and that their cancer prevention cancelling needs improvement [42,71]. Unsurprisingly, 54.9% of our respondents listed the need for promoting free screening tests among their most important unmet healthcare needs.…”
Section: Healthcare Staff and A Key Role Of Gps As Health Promoterssupporting
confidence: 83%
“…Currently, a “healthy lifestyle” is defined as having sufficient physical activity, a well balanced diet, a Body Mass Index (BMI) within the recommended range, a non or moderate consumption of alcohol, being a non-smoker and obtaining sufficient daily sleep ( Znyk et al, 2019 , Liu et al, 2016 ). These six health-related lifestyle factors have often been assessed in the general adult population, and several studies showed that a majority of individuals presented multiple health risk behaviours ( Liu et al, 2016 , Ford et al, 2012 , John et al, 2018 Apr 27 , Poortinga, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although physicians are supposed to recommend healthy behaviours to their patients, they themselves do not always meet these criteria ( Wilf Miron et al, 2019 , Borgan et al, 2015 , Frank et al, 1998 , Bakhshi and While, 2013 ). A recent study carried out in Poland showed that only 11% of general practitioners (GPs) met the criteria for five healthy lifestyle factors assessed (a non or moderate alcohol consumption, a non-smoking status, a BMI within the normal range, a healthy diet, and sufficient physical activity) ( Znyk et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation